The Impact of Digitalization of Payment Systems on Inflation Stability in Indonesia - Shintami Oktavia; Loranty Folia Simanjuntak; Muhammad Alhasymi Matondang; Richna Handriyani (Outline Journal of Economic Studies, 2025)
This study aims to analyze the impact of payment system digitization on inflation stability in Indonesia during the period 2015 - 2024 using a qualitative approach. The main focus of this research is to examine how digital transformation in the payment system, especially through the use of e-money, QRIS, debit cards, and credit cards can contribute to changes in transaction patterns in society and its implications for the inflation rate. Digital transformation in the national payment system, such as the increasing use of QRIS, e-money, and other non-cash payment methods has changed people's transaction behavior and strengthened the effectiveness of inflation control policies. Digitalization accelerates transaction efficiency, lowers the amount of distribution costs, and expands financial inclusion. It also collectively contributes to price stability. However, there are challenges such as digital infrastructure gaps and financial literacy that still need to be improved, so that the benefits of digitalization can be used by many people as users. The results of this study confirm that the digitization of payment systems is a strategic instrument in maintaining Indonesia's macroeconomic stability, as long as there is synergistic policy support and continuous education.